EXPERIENCE OF CARE NURSES: APPROACHES TO THE PRINCIPLES OF NAVIGATION OF CANCER PATIENTS - Roque, Andréa Cibele [UNESP]; Gonçalves, Ivana Regina [UNESP]; Popim, Regina Célia [UNESP] (FapUNIFESP (SciELO), 2023)
Objective: To understand the experiences of nurses assisting cancer patients, according to Harold Freeman´s principles of navigation. Method: A qualitative study conducted in a large public hospital in the State of São Paulo in December 2021. Six nurses were interviewed using a semi-structured script with questions about the care of cancer patients and their families. The data were submitted to content analysis with theoretical framework of Harold Freeman. Results: Five categories emerged from the statements: fluidity in care; integration between teams; bond with patients and families; competencies of care nurses in the navigation of cancer patients; valorization and facilities in team training. Conclusion: According to the categories observed, we can consider that the experiences of care nurses working in an oncology unit revealed the strengthening of navigation principles contributing to the care and minimization of barriers, which can facilitate and/or soften the therapeutic path of the cancer patient.
EXPERIENCIA DE ENFERMEROS DE CUIDADO: APROXIMACIONES A LOS PRINCIPIOS DE NAVEGACIÓN DE PACIENTES CON CÁNCER
EXPERIÊNCIA DE ENFERMEIRAS ASSISTENCIAIS: APROXIMAÇÕES AOS PRINCÍPIOS DA NAVEGAÇÃO DE PACIENTES ONCOLÓGICOS
Keywords: Cancers; Hospital oncology service; Nursing; Patient navigation; Patient-centered care